CCBuilder: a software that produces synthetic microstructures of WC-Co cemented carbides. (January 2019) - Johansson, Sven A.E.; Öhman, Mikael; Ekh, Magnus; Wahnström, Göran
Abstract: In this paper, the software CCBuilder and its methods to generate synthetic three-dimensional (3D) microstructures of WC-Co cemented carbides are presented. Generating synthetic microstructures is critical, as it enables accurate virtual testing where influences from microstructural parameters can be investigated in a systematic and controlled way. The model of the microstructure is based on a voxel description of the material volume and the WC grains are represented as truncated triangular prisms. The grains are inserted into the simulation domain and to obtain a realistic microstructure a combination of packing and a Monte Carlo Potts simulation is used. The orientations of all individual WC grains are known and it is shown that the microstructure is built up of two interpenetrating networks, the WC grains and the Co phase. Numerical studies are presented to show how input parameters to CCBuilder, such as grain size, grain shape, packing strategy, voxel density, system size, and Monte-Carlo steps affect the resulting simulated microstructure. The obtained microstructures are geometrically realistic and the contiguity of the carbide phase shows very good agreement with published experimental data. Highlights: A software CCBuilder to generate synthetic 3D microstructures of WC-Co is presented. The methodology to generate the microstructures is discussed. CCBuilder combines various packing strategies with a Monte Carlo Potts simulation. Studies are presented of how input to CCBuilder affects the resulting microstructure. The contiguity of the carbide phase shows very good agreement with experimental data.